Mid-Neoproterozoic mafic rocks in the western Jiangnan orogen, South China: Intracontinental rifting or subduction?. (November 2019) - Wan, Le; Zeng, Zuoxun; Asimow, Paul D.; Zeng, Zhihui; Peng, Lianhong; Xu, Daliang; Wei, Yunxu; Liu, Wei; Lu, Chengdong; Chang, Wenqi
Graphical abstract: Highlights: There are 757 Ma high-Ti tholeiitic basalts in the western Jiangnan orogen, Hunan Province. The 757 Ma magmas formed in an intracontinental rift rather than a mantle plume. Divergent double-sided subduction followed by collision formed the Jiangnan orogen. Observations support placement of the South China Block along the margin of Rodinia. Abstract: Widely distributed Meso- to Neoproterozoic igneous rocks record the evolution of the Jiangnan orogen. We present integrated geochemical and geochronological data for basalts from the Gaoqiao area, northwestern Hunan Province. U-Pb dating of zircons indicates that the formation of Gaoqiao basalts occurred in the Neoproterozoic, no earlier than 757 ± 16 Ma. Like the contemporaneous mafic rocks in neighboring areas, the Gaoqiao basalts show trace element characteristics suggesting derivation from a source similar to ocean-island basalts (OIBs), including strong enrichment in large-ion lithophile elements (LILEs), high-field strength elements (HFSEs) and TiO2, and high Ti/Y ratios. Placed in a regional tectonic context, however, the Gaoqiao suite is most consistent with an intracontinental rift model and offers no support to the idea of ongoing subduction in middle-late Mid-Neoproterozoic time in the western Jiangnan orogen. Despite the coincidence between the age of this rift and the separation of East Antarctica-Australia from Laurentia, we argue that the rift recorded in the South China Block (SCB) was an independent and probably unrelated event during the break-up of the Rodinia supercontinent.